Sob o risco do gênero: clausuras, rasuras e afetos de um cinema com mulheres - Carla Ludmila Maia Martins (2015)
The thesis addresses some films made by women through descriptive and comparative analyses, seeking to contribute to contemporary Brazilian documentarys critical fortune and resuming some theoretical formulations of feminist thought. The selected films, besides female authors, have in common the encounter with other women before the camera, as instance of invention and research. We part from such generality towards a more specific approach, analysing how each one enacts its relations through different features and strategies. Gender is considered a risk, in both senses of the term: as danger it is what can lead to enclosures, fixed determinations, undermining the production of differences by procedures of identification, as trace, it is what marks and erasure its own definition, evoking the thought about otherness. Thence the need of thinking film with women rather than Womans film: focusing on relational aspects of each work, both regarding the relations between directors and characters and between film and viewer, we aim to indicate not categorizations but distribution spaces created by each work. It is important to bear in mind that Women Studies field is agonistic, it doesnt rest in definitions and certainties, it is in constant dispute. The objective of this thesis is finally observe how films with women take partof this dispute, either by listing vicinities, either by showing impasses, and critically reflect on the aesthetic, ethical and political potentialities that a cinema marked by women's perspectives can bring into action.